A biography of power : research and excavations at the Iron Age oppidum of Bagendon, Gloucestershire (1979-2017) - Moore, Tom (Archaeopress Archaeology, 2020)
This title explores the changing nature of power and identity from the Iron Age to the Roman period in Britain. It provides fresh insights into the origins and nature of one of the lesser-known, but perhaps most significant, Late Iron Age 'oppida' in Britain - Bagendon in Gloucestershire.